2018
DOI: 10.14202/vetworld.2018.248-253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of levamisole, Vitamin E, and selenium against aflatoxicosis in broilers chicken

Abstract: Aim:The experiment was conducted to determine of levamisole (0.2 ml/kg-BW), Vitamin E (80 mg)+selenium (1.6 mg), and aflatoxin (B1) (positive control) compared with group without aflatoxin (negative control) on some liver enzymes (aspartate transaminase [AST] and alanine transaminase [ALT]), as well as to study the histopathological changes.Materials and Methods:The experiment included (200) 1-day-old broilers Ross 308 (Turkey source) mixed sexes. They were divided into four equal groups (50 chicks each group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…Elevated levels of serum AST and GGT were observed in birds receiving 0.5 ppm of AF as compared to control group chickens, indicating considerable damage to the liver. Similar findings of elevated activities of serum enzymes due to aflatoxicosis were observed by many researchers [25][26][27]). Raju and Devegowda (2000) recorded no difference in AST levels in birds fed AF up to 0.3 ppm for 21 days [25].…”
Section: Discussionsupporting
confidence: 88%
“…Elevated levels of serum AST and GGT were observed in birds receiving 0.5 ppm of AF as compared to control group chickens, indicating considerable damage to the liver. Similar findings of elevated activities of serum enzymes due to aflatoxicosis were observed by many researchers [25][26][27]). Raju and Devegowda (2000) recorded no difference in AST levels in birds fed AF up to 0.3 ppm for 21 days [25].…”
Section: Discussionsupporting
confidence: 88%
“…The MDA levels in the blood, liver, heart, and pectoral muscles were remarkably elevated, whereas the levels of antioxidants indices GSH-Px, T-AOC, T-SOD, and CAT as well as mRNA expression of antioxidant genes GPx-1 , GPx-2 , GPx-4 , DIO-1 , and SOD-1 in the liver of chicks (day 1 and 14) were reduced in the control group, however, the supplementation of the combination of dietary Q + VE reverted the oxidative stress effects in the blood, liver, heart, and pectoral muscles by elevating the levels of antioxidants indices GSH-Px, T-AOC, T-SOD, and CAT, and upregulates the antioxidant genes GPx-1 , GPx-2 , GPx-4 , DIO-1 , and SOD-1 at both time points. These results were consistent with the studies by Ulaiwi (2018) and Torki et al (2018) which reported that the combination of levamisole, vitamin E, and selenium and quercetin, oat hulls, β-glucans, lysozyme, and fish oil, respectively reduce oxidative stress in broiler chicks.…”
Section: Discussionsupporting
confidence: 93%
“…The summary effect size is denoted by the blue diamond. References: Liu et al [ 29 ], Subhani et al [ 26 ], Rajput et al [ 28 ], Sridhar et al [ 30 ], Solis-Cruz et al [ 25 ], Sridhar et al [ 32 ], Bintvihok et al [ 34 ], Sadeghi et al [ 31 ], Muhammad et al [ 33 ], Nabi et al [ 21 ], Cao et al [ 8 ], Almusawi et al [ 24 ], Malekinezhad et al [ 22 ], Rashidi et al [ 23 ], Ulaiwi et al [ 27 ], Lin et al [ 19 ], Mesgar et al [ 20 ], Muhammad et al [ 33 ], Rashidi et al [ 23 ], Pappas et al [ 44 ], Allameh et al [ 5 ], Almusawi et al [ 24 ], Mahrose et al [ 41 ], Pappas et al [ 44 ], Barati et al [ 7 ], Rashidi et al [ 23 ], Valchev et al [ 42 ], Xie et al [ 4 ], Stanley et al [ 40 ], Ejiofor et al [ 36 ], Allameh et al [ 5 ], Motawe et al [ 38 ], Barati et al [ 7 ], Rashidi et al [ 23 ], Basmacioglu et al [ 39 ], Hernandez-Ramires et al [ 36 ], Solis-Cruz et al [ 25 ], Cao et al [ 8 ], Salem et al [ 37 ], Barati et al [ 7 ], Ulaiwi et al [ 27 ], Mahrose et al [ 41 ], Pappas et al [ 44 ].…”
Section: Figurementioning
confidence: 99%